2021
DOI: 10.1007/s10875-021-01036-0
|View full text |Cite
|
Sign up to set email alerts
|

Neutralizing Autoantibodies to Type I IFNs in >10% of Patients with Severe COVID-19 Pneumonia Hospitalized in Madrid, Spain

Abstract: Background In a recent study, autoantibodies neutralizing type I interferons (IFNs) were present in at least 10% of cases of critical COVID-19 pneumonia. These autoantibodies neutralized most type I IFNs but rarely IFN-beta. Objectives We aimed to define the prevalence of autoantibodies neutralizing type I IFN in a cohort of patients with severe COVID-19 pneumonia treated with IFN-beta-1b during hospitalization and to analyze their impact on various clinical variables and outcomes. Methods We analyzed stored s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

21
104
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 117 publications
(128 citation statements)
references
References 31 publications
21
104
0
3
Order By: Relevance
“…The full engagement status was significantly less frequent in patient with auto-Abs than in patients without auto-Abs. but like other studies [7,9], there was no difference for comorbidities. Unlike study of Troya et al [7], where a significant correlation between presence of auto-Abs neutralizing type I IFNs, raised levels of C-Protein Reactive and low lymphocytes counts was observed, in our study, no difference was seen for these biological characteristics.…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…The full engagement status was significantly less frequent in patient with auto-Abs than in patients without auto-Abs. but like other studies [7,9], there was no difference for comorbidities. Unlike study of Troya et al [7], where a significant correlation between presence of auto-Abs neutralizing type I IFNs, raised levels of C-Protein Reactive and low lymphocytes counts was observed, in our study, no difference was seen for these biological characteristics.…”
Section: Discussionsupporting
confidence: 70%
“…but like other studies [7,9], there was no difference for comorbidities. Unlike study of Troya et al [7], where a significant correlation between presence of auto-Abs neutralizing type I IFNs, raised levels of C-Protein Reactive and low lymphocytes counts was observed, in our study, no difference was seen for these biological characteristics. It is nevertheless important to note that we compare biological characteristics obtained at hospital admission, and not maximum levels of C-Protein Reactive and minimum levels of lymphocytes count.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Furthermore, pegylated IFNα2a therapy in patients with inborn errors of type I IFN immunity prevented severe COVID-19 disease 46 . In addition to the impaired type I IFN response triggered by SARS-CoV-2, recent studies have demonstrated the development of autoantibodies that can neutralize type I IFNs 44,47 . To evade the antiviral effects of type I IFNs, viruses have evolved various strategies to suppress IFN induction.…”
Section: Discussionmentioning
confidence: 99%
“…Dysregulation of the IFN response in SARS-CoV-2 infection can be driven by both direct viral antagonism of innate immune mechanisms, as well as by host characteristics such as age, genetics and other comorbidities 20 . Additionally, several studies have identified autoantibodies against IFN as a significant negative survival factor for severe COVID-19, further emphasizing the prominent role of IFN in SARS-CoV-2 pathogenesis and clearance [21][22][23][24] . Importantly, IFNmediated effects may also be detrimental to COVID-19 outcomes.…”
Section: Introductionmentioning
confidence: 99%